Pengaruh Pengambilan Keputusan Bersama terhadap Kadar Glukosa dan HbA1c pada Pasien Diabetes Mellitus: Tinjauan Literatur - Hilmawati, Febriana; Karuniawati , Hidayah (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2025)
Background: Diabetes mellitus (DM) is a chronic disease with a high global prevalence, requiring comprehensive and patient-centered care. Shared Decision Making (SDM) is a collaborative approach between patients and healthcare providers that has been associated with improved treatment adherence and clinical outcomes in chronic diseases. Objective: This literature review aimed to evaluate the impact of SDM on glycemic control, particularly blood glucose and HbA1c levels, in patients with diabetes mellitus. Methods: A systematic search was conducted on PubMed and Scopus databases using specific keywords, limited to randomized controlled trials (RCTs) published in English between 2015 and 2025. Inclusion criteria included adult patients with type 1 or type 2 DM, SDM as the primary intervention, and HbA1c or blood glucose levels as clinical outcomes. Results: Five RCTs met the eligibility criteria. Most studies reported a decrease in HbA1c in the intervention group, although only one study showed a statistically significant within-group reduction. No consistent significant differences were observed between the intervention and control groups. However, SDM was positively associated with improved patient engagement, satisfaction, and the quality of communication. Conclusion: While evidence regarding the direct impact of SDM on HbA1c remains inconclusive, SDM appears to enhance patient participation and therapeutic communication in diabetes care. Further standardized and long-term studies are needed to confirm its clinical effectiveness.